Robotics, stem & IoT: leading the Malaysian student generation towards a sustainable future / Tuan Norhafizah Tuan Zakaria - Tuan Zakaria, Tuan Norhafizah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Robotics, a discipline within computer science and engineering, emphasizes the design, construction, and control of intelligent mechanical devices. Interest in robotics has been growing, not just among university students but also at the school level. Early exposure to robotics often begins in primary schools through various competitions, offering students the chance to delve into this rapidly advancing field. The Malaysian Ministry of Education has established numerous platforms and competitions to nurture students' skills in robotics. Additionally, these contests incorporate elements of STEM (Science, Technology, Engineering, and Mathematics), the Internet of Things (IoT), and the Sustainable Development Goals (SDGs). Participation in robotic competitions offers numerous benefits for students, enhancing both their academic and personal development. These events improve students' communication, teamwork, problem-solving, and critical thinking skills [1][2]. They also increase interest in robotics, programming, and STEM subjects while fostering social skills and creating bonds between participants [3] [4]. Robotic competitions boost students' self-confidence and robot knowledge [1], serving as a valuable tool for educators [4]. The collaborative nature of these events is crucial for their educational impact, with teamwork being a prerequisite for success [3]. Moreover, participation in international competitions like EUROBOT can significantly increase student motivation and provide opportunities to develop transversal skills in university studies [2].